Strategy and commitments to institutional logics: Organizational heterogeneity in business models and governance. (November 2016) - Ocasio, William; Radoynovska, Nevena
Theory and research on institutional pluralism and complexity provide an opportunity to re-examine a key question of strategy: the sources of organizational heterogeneity in the creation and capture of value. Concretely, we focus on the implications for value creation and capture in terms of organizations' business models and governance strategies, respectively. We posit that strategic organizational choices are shaped by available institutional logics and theorize that greater institutional pluralism leads to increased heterogeneity—rather than isomorphism—in business models and governance strategies. As the mechanism for heterogeneity, we explain how pluralism leads to differentiated organizational commitments to distinct combinations and prioritizations of institutional logics. The article further examines how institutional complexity, wherein latent contradictions between logics become salient, provides opportunities for strategic change. We theorize that framing exposed contradictions as incompatible or paradoxical implies differentiated outcomes with respect to transformations in organizations' business models and governance strategies.